PENERAPAN PRINSIP SYARIAH DALAM PERMODALAN BANK SYARIAH - Danang Wahyu Muhammad (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Islamic Bank is a bank that is based on Syariah principles. The principles must always be obeyed both in the establishment and in the operational, including the financial capital. Regarding the capital, it must not come from a source that is considered as haram according to Syariah principles, which will cause a mix between halal and haram. Something that is halal must be strictly separated from something that is haram, and vice versa. This paper discusses The Application of Syariah Principles in Islamic Bank Capitalization. Several principles are applied and must be obeyed by Islamic Bank, namely: Al-Ta’awan Principle, Principle of Avoiding (Al-Ikhtinaz) from gharar, masyir, and riba. As a part of Islamic Economy, the activities of Islamic Bank can be observed from four points of view, namely; ilahiyah economy, ahlaq economy, humanity economy, and balance economy. Meanwhile, from several viewsnof Muslim Economists, it can be concluded that the core of Islamic teaching is tauhid, which means that all human activities in the world, including economy, is merely for ibadah – act of devotion – which is aimed at following one law, Allah’s law. The value of tauhid, in practice, is interpreted in many valaes and there are three basic values that become distinguishing factors between Islamic economy and other, namely adl, khilafah, and takaful. It can be conladed that is a possibility that Syariah Principles are violated by Islamic Bank in terms of its capitalization. This can be see from the missing of requirements that make it compulsory for all founders to make a statement letter which states that the financial capital deposited to Islamic Bank does not come from a source which is considered as haram according to Syariah Principle. The consequence of the missing requirement is the possibility of receiving haram financial capital from the founders. Should this happen, then Syariah Principle is violated.